(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The larger grain borer, Prostephanus truncatus (Hom), one of the main pests of stored grain in tropical and subtropical areas, widely diffused in Africa on maize cobs and dried cassava, is recorded for the first time in Italy, in a bakery of eastern Sicily. Some data on the biology, morphology and distribution are provided.